Evaluation of Forklift Workers’ Perception Accuracy of the Carried Cargo Weight Using a Virtual Reality Simulator - Nobuyoshi Hashimoto; Wataru Wakita; Susumu Okumura; Takuma Saga (IEEE Access)
This study evaluated the accuracy of weight perception of cargo carried on forklifts with the aim of developing a virtual reality training simulator for forklift work safety and efficiency. In the developed simulator, users with a head-mounted display can experience virtual forklift operations using the operating equipment in a cab mock-up. The virtual forklift has parameters that determine the behaviors of the fork and vehicle body, which are set based on actual measurements; therefore, it is highly reproducible. The simulator is the first to incorporate cargo weight perception based on fork behavior and seat tilt. We conducted an experiment in which 13 workers and 13 beginners compared the weights of two cargos on the simulator. The results showed that, under the same conditions, workers and beginners had an average correct response rate of 76.9% and 64.0%, respectively. The incorrect response rate for weight perception decreased exponentially as the employment term increased. Workers perceived cargo weight through the fork behavior and seat tilt, with dominance varying among individuals, categorizing them into three groups: seven with dominant fork behavior, four with dominant seat tilt, and two with both dominant behaviors. The cross-modal effect of combining fork behavior and seat tilt was confirmed. It was suggested the accuracy may decrease if the operator is not aware of which sense was more important. These findings indicate that forklift workers can improve their work safety and efficiency by understanding their own perceptual characteristics.